2020
DOI: 10.1002/ags3.12401
|View full text |Cite
|
Sign up to set email alerts
|

Robotic surgery for colorectal cancer

Abstract: Throughout its more than 20 years of activity, surgical robot systems have been incorporating different improvements that replace the inherent limitations of laparoscopic surgery. Some of these improvements consist of changes in the ergonomics and reproduction of hand movements with articulated instruments. In addition, infrared technology and slimmer arms have been incorporated to facilitate procedures in multiple abdominal quadrants without requiring repositioning. This development in technology has meant th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 43 publications
0
32
0
Order By: Relevance
“…Longer operation time is one of the demerits of robotic surgery. Previous literatures show longer operative time for robotic surgery with significant differences from open or laparoscopic surgery 12 . However, Jan and Kim reported that robot TME has a shorter learning curve 13 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Longer operation time is one of the demerits of robotic surgery. Previous literatures show longer operative time for robotic surgery with significant differences from open or laparoscopic surgery 12 . However, Jan and Kim reported that robot TME has a shorter learning curve 13 .…”
Section: Discussionmentioning
confidence: 98%
“…Previous literatures show longer operative time for robotic surgery with significant differences from open or laparoscopic surgery. 12 However, Jan and Kim reported that robot TME has a shorter learning curve. 13 We have performed 74 robotassisted laparoscopic rectal cancer surgeries in this period by four operators.…”
Section: Discussionmentioning
confidence: 99%
“… 16 , 17 , 18 , 19 Robotic systems are a promising advanced technology that could overcome some of the inherent limitations of laparoscopic surgery for rectal cancer, providing high‐quality three‐dimensional images, articulating instruments, stable camera work, and motion scale function. 20 , 21 The ROLARR trial was performed in a multicenter setting to compare robotic‐assisted and conventional laparoscopic rectal cancer surgery, indicating that robotic‐assisted laparoscopic surgery did not significantly reduce the risk of conversion to open laparotomy (8.1% vs 12.2%). 22 However, a retrospective cohort study based on the National Clinical Database in Japan found a significantly lower conversion rate to open surgery in robot‐assisted laparoscopic surgery than in conventional laparoscopic low anterior resection (0.7% vs 2.0%), less intraoperative blood loss (15 ml vs 20 ml), and a shorter postoperative hospital stay (13 d vs 14 d).…”
Section: Surgery For Rectal Cancermentioning
confidence: 99%
“…[1][2][3] RS has undergone many new improvements, including three-dimensional visualization and articulated instruments that assist in complex and precise movements, but energy device options are not as abundant for RS as for conventional LS. 1 In addition, considering costs, RS for rectal cancer often relies only on monopolar scissors (MS) without a bipolar vessel sealing device (BVSD) or ultrasonic coagulating shears (USC). 4,5 Results of a meta-analysis have shown that RS for rectal cancer is acceptable in terms of perioperative complications compared with conventional LS.…”
Section: Introductionmentioning
confidence: 99%
“…Robotic surgery (RS) for rectal cancer has rapidly increased in recent years and can safely provide oncological outcomes comparable to conventional laparoscopic surgery (LS) 1–3 . RS has undergone many new improvements, including three‐dimensional visualization and articulated instruments that assist in complex and precise movements, but energy device options are not as abundant for RS as for conventional LS 1 . In addition, considering costs, RS for rectal cancer often relies only on monopolar scissors (MS) without a bipolar vessel sealing device (BVSD) or ultrasonic coagulating shears (USC) 4,5 …”
Section: Introductionmentioning
confidence: 99%